1984
DOI: 10.1007/bf00329934
|View full text |Cite
|
Sign up to set email alerts
|

The unusual structure of heat shock locus 2-48B in Drosophila hydei

Abstract: We have previously isolated a 500 bp-long cDNA clone, NO9-15, which is derived from a nuclear transcript originating from the heat shock locus 2-48B of Drosophila hydei (Peters et al. 1982). Sequence analysis shows that this clone carries 4 complete copies and 1 partial copy of a 115 bp repeat unit. The repeats are closely homologous with a maximal sequence divergence of about 10%. The sequence does not contain an open reading frame. The genomic organization of heat shock locus 2-48B, as probed with the cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Some of our results have been reported previously (Ranz et al 1997 and are included here for the sake of completeness only. Two additional genes mapped by other authors, Hsr (Peters et al 1984) and orb (H. Naveira, pers. comm.…”
Section: Chief Map Featuresmentioning
confidence: 88%
See 1 more Smart Citation
“…Some of our results have been reported previously (Ranz et al 1997 and are included here for the sake of completeness only. Two additional genes mapped by other authors, Hsr (Peters et al 1984) and orb (H. Naveira, pers. comm.…”
Section: Chief Map Featuresmentioning
confidence: 88%
“…Their estimated sizes in D. melanogaster are indicated. Two genes localized by other authors, Hsr (Peters et al 1984) and orb (H. Naveira, pers. comm.…”
Section: Chief Map Featuresmentioning
confidence: 92%
“…At the moment we have no indication as to the promoter site used and possible processing and termination sites needed. The corresponding gene locus in Drosophila hydei, 48BC, (Peters et al 1984) also contains a long region comprised of repetitive sequences. A direct comparison of the sequences and the physical structure contained in both repeats might give insight into the relevant features of this highly interesting RNA class.…”
Section: Discussionmentioning
confidence: 99%
“…Cloning of some sequences from the 2-48B puff of D. hydei (Peters et al 1980) indicated certain unusual features of this puff, which were further confirmed by a more detailed characterization of several clones from this region (Peters et al 1984). In the same year, cloning of the 93D puff sequences using micro-dissection of polytene chromosomes of D. melanogaster was reported (Walldorf et al 1984).…”
Section: A Homolog Of the 93d Puff Is Present In Differentmentioning
confidence: 80%